สมรรถนะของผู้บริหารโรงเรียนโครงการพัฒนาประเทศไทยเป็นศูนย์กลางการศึกษา ในภูมิภาคอาเซียน (Education Hub) สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - Pilayon, Chanidaporn; Indusuta, Kanyamon (Journal of Graduate School Sakon Nakhon Rajabhat University, 2021)
The purposes of this research were to study and compare the perspectives of educational personnel toward the competency of administrators in schools within the Thailand development project as an education hub in the ASEAN region under the Office of the Basic Education Commission, as classified by educational background and work experience. The sample, obtained through stratified random sampling, consisted of 150 educational personnel in schools that offered international programs within the Thailand development project as an education hub in the ASEAN region under the Office of the Basic Education Commission in the academic year 2020. The research instrument was a set of 5-point rating scale questionnaires with the index of item objective congruence (IOC) of 1.0 and a level of reliability at 0.99. The data were analyzed through the descriptive statistics, t-test and One-Way ANOVA and Scheffé’s post hoc comparison method. The research results were as follows: 1. The perspectives of educational personnel toward the competency of school administrators were at a high level. 2. The perspectives of educational personnel toward the competency of administrators, classified by different educational background and work experience as a whole and in each aspect were different.